Vous êtes sur la page 1sur 11

ν˜ S f t2

ν˜ ν/ν˜ = 3 5 ν˜ f t2

S

S

ν˜

f t2 S ν˜

ν t

ν t = ν˜ f v1 ,

f v1 =

χ 3

χ 3 + c

3

v1

,

χ ν˜ ,

ν

ν ν˜

˜

Dt

1

= P D + T + σ ∇ · ((ν + ν˜)ν˜) + c b2 (ν˜) 2 ,

P = c b1 (1 f t2 ) Sν,˜

S

S S +

D = c w1 f w

c

b1

κ

2

f t2 ν˜ d 2

,

ν˜ d 2 f v2 ,

κ

2

f v2 = 1

χ χf v1 ,

1 +

T = f t1 (∆u) 2

S d f w

f w = g

1 + c g 6 + c

w3 1/6 ,

w3

6

6

g = r + c w2 (r 6 r),

f t1 = c t1 g t exp c t2 u 2 d 2 + g d ,

ω

t

2

t

2

t

r = min

ν˜ 2 d 2 , r lim .

f t2 = c t3 exp c t4 χ 2 ,

g t = min(0.1, u/ω t x) d t ω t u x c b1 = 0.1355 σ = 2/3 c b2 = 0.622 κ = 0.41 c w1 = c b1 2 + (1 + c b2 ) c w2 = 0.3 c w3 = 2 c v1 = 7.1 c t1 = 1 c t2 = 2 c t3 = 1.2 c t4 = 0.5 r lim = 10 ν˜

ν˜ = 0

∂ν˜ n = 0

ν/ν˜ = (ν t ) ν/ν˜ 1

0 =

ρ ∗ { } + ν˜ ∗ { }

= ∂ρν˜

∂t

˜) ρ(P D + T) 1

+ ∇ · (ρ

σ ∇ · ρ(ν + ν˜)ν˜

c

b2

σ

1

ρ (ν˜) 2 + σ (ν + ν˜)ρ · ∇ν˜

ρ u µ = ν/ρ ν˜ ν˜

ρu [[˜ν]] = 2

1

c b2

σ

ρ

∂ν˜

∂x

2

1

σ (ν + ν˜)

∂ρ ∂ν˜

∂x ∂x

x

x u ν˜ ν ν˜ ν˜ ν t ν f v1

f t2 ν˜

f t2 ν˜ f t1 ν˜ ν/ν˜ = f t2 f t2

f t2 ν/ν˜ = log(c t3 )/c t4 0.6 ν/ν˜ = 1.34 f t2 f t2 c t3 = 0 ν/ν˜ = 3 ν˜ ν t

ν˜

ν˜ χ = 10 5 2×10 5 x χ max 0.00059Re x 0.83 Re x x x

χ max 0.0227Re c C d x

C M χ max 0.037Re C M Re C M

S

S 0.3S S S f v2 χ S S S > 0.3S S C 1

ν˜ d 2 f v2

S =

S + S

S +

S(c v2 S + c v3 S)

2

(c v3 2c v2 )S S

:

:

S

S <

c v2 S

c v2 S

c v2 = 0.7 c v3 = 0.9 c v2

S S = (1 c v2 )S c v3

S f v3

S (1 c v3 )S

S/S → −∞.

S/S

1.0

0.9

0.8

0.7

0.6

0.5

0.4

0.3

0.2

0.1

0.0

-3

-2

-1

S

S/S

0

ν˜ = 0 ν˜ = 0 2 ν˜ 0 ∂ν/∂t˜ 0 O((ν + ν˜ )/u) u ν˜ ν˜ < ν ν˜ ν˜ ν˜

ν˜ 0

ν˜

C 1 ν˜ ν˜ = 0

˜

Dt

1

= P n D n + σ ∇ · [(ν + νf˜

n )ν˜] + c b2

σ

(ν˜) 2

P n D n f n (χ) C 1 ν˜ = 0

n 0 = D n 0 = 0,

P

P n

∂ν˜

0

=

c b1 (1 c t3 )S,

D n

∂ν˜

0

= 0

f n (0) = 1,

f n

∂χ

0

 = 0

ν˜ ν˜

Dt

D

1

2 ν˜ 2 = ν˜ P n D n + σ ∇ · [(ν + νf˜

1

n )ν˜] + c b2

σ

(ν˜) 2

=

ν˜(P n D n ) +

1

σ

∇ · (ν + νf˜

n ) 2 ν˜ 2

1

1

σ [ν + ν˜(f n c b2 )] (ν˜) 2

n D n 0,

P

1 + χ(f n c b2 ) 0.

ν˜ = 0 2 ν˜ 0

1

n D n + σ (ν

P

+

νf˜ n )2 ν˜ = 0

n D n 0,

P

1 + χf n 0.

C 1 |ν˜| f n 1 ν + ν˜ ν + |ν˜|

f n = c n1 + χ 3

χ 3

c n1 = 16 ν + νf˜ n c n1 16.46 f t2 ν˜ = 0 c t3 > 1 P n ν˜

c n1

P n = c b1 (1 c t3 )Sν,˜

D n = c w1 ν˜ d 2

P n S

d S/ν f t2 ν˜ P n f t2

S

D n

ν˜ d S/ν

f n

C 1 P n < 0 χ ν˜

1.0

0.8

0.6

0.4

0.2

0.0

-0.2

-0.4

-0.6

-0.8

-1.0 -10

-8

-6

-4

-2

0

5.0

4.5

4.0

3.5

3.0

2.5

2.0

1.5

1.0

0.5

0.0

1 + χf n
1 + χ

-5

-4

-3

-2

-1

0

1

χ

χ

∂ ν/∂n˜ = 0 ν˜ = 0 d = 0 y = 0 v

u v ∂u/∂y ∂ν/∂n˜ = 0 ν˜

u v

P

νS

0.55

0.50

0.45

0.40

0.35

0.30

0.25

0.20

0.15

0.10

0.05

0.00

-0.05

3 = 0

f t2 c t

f t2

-2

-1

0

1

2

3

d S/ν = 100

χ

4

ν˜ = 0 d = |y| ν˜

ν˜ = κu τ y,

S = u τ

κy ,

u τ y κ = 0.41 f v1 S u(y) ∂/∂x ∂/∂y x

y u = u(y) ν˜ = ν˜(y) x

dy (ν + ν t ) du = 0,

d

dy

(ν + ν t ) du dy

2

= = u τ ,

u τ

2

1

dy (ν + ν˜) dν˜

dy

d

+ c b2

σ

˜

dy

2

+ c b1 (1 f t2 ) ˜ c w1 f w

f v1 =

χ 3

χ 3 + c

3

v1

,

χ

c

b1

κ

2

f t2

ν˜

y

σ

ν˜ ,

ν

ν t = ν˜ f v1 ,

S

= du

ν˜

dy + κ 2 y 2 f v2 ,

f v2 = 1

χ

1 + χf v1 ,

f t2 = c t3 exp c t4 χ 2 .

= 0,

y + yu τ u + u/u τ

χ = κy + ,

S + =

ν

u

2

τ

S =

1

κy + .

ν

t

ν

=

κy + ,

du +

dy + =

1

κy + ,

y + 1.

ν˜ S f v1 f v2 r f v1 f t2 x S

du +

dy +

=

c

v1 + (κy + ) 3

3

3

c v1 + (κy + ) 3 (1 + κy + )

u(0) = 0

u + (y + ) =

4

i=1

c

v1 + z

3

3

i

4z i ) log κy + z i log (z i ) ,

κz

2

i

(3 +

z i

c

3

v1 + z

3

i

+ z

4

i

= 0

u + (y + ) = B + c 1 log (y + + a 1 ) 2 + b 2 c 2 log (y + + a 2 ) 2 + b 2

1

2

c 3 [y + + a 1 , b 1 ] c 4 [y + + a 2 , b 2 ],

[x, y] (y, x) κ = 0.41 c v1 = 7.1

B = 5.0333908790505579 a 1 = 8.148221580024245 a 2 = 6.9287093849022945 c 1 = 2.5496773539754747 c 3 = 3.599459109332379

b 1 = 7.4600876082527945 b 2 = 7.468145790401841 c 2 = 1.3301651588535228 c 4 = 3.6397531868684494

y +

u +

1

κ log y + + 1 + B,

du +

1

dy +

κy + + 1

,

y + → ∞.

y + = u + + exp(κB) exp(κu + ) 1 κu +

2 1 (κu + ) 2 1 6 (κu + ) 3 .

κ = 0.41 B = 5 B c v1 = 7.1

u
20
15
S
A
10
S
A asymptotic
Spalding
5
0.5
1.0
1.5
2.0
2.5
3.0

log y log 10